2016
DOI: 10.1037/dhe0000023
|View full text |Cite
|
Sign up to set email alerts
|

California DREAMers: Activism, identity, and empowerment among undocumented college students.

Abstract: There is a large gap in college access and success for undocumented students. This emergent population remains uniquely and precariously situated within campus environments, despite the passage of Development, Relief, and Education for Alien Minors (DREAM) Acts in some states. These inequities have sparked activism for DREAMers associated with the undocumented youth movement. Using data from interviews of 16 undocumented students at a selective California research institution, this study explores the ways in w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(56 citation statements)
references
References 26 publications
3
53
0
Order By: Relevance
“…No longer are such groups of young people willing to sit on the periphery of society as political and social changes are made that directly affect their well‐being, their livelihood, and their status as U.S. citizens (Forenza, Roger, & Lardier, ). Most importantly, these young people, and youth like them, have a strong sense of their ethnic group and cultural identity, which works as a process toward unity and collective engagement and identity (DeAngelo, Schuster, & Stebleton, ). Most scholarship misses this reality, deeming young people incapable of such broad‐based change (Christens & Speer, ).…”
Section: Introductionmentioning
confidence: 99%
“…No longer are such groups of young people willing to sit on the periphery of society as political and social changes are made that directly affect their well‐being, their livelihood, and their status as U.S. citizens (Forenza, Roger, & Lardier, ). Most importantly, these young people, and youth like them, have a strong sense of their ethnic group and cultural identity, which works as a process toward unity and collective engagement and identity (DeAngelo, Schuster, & Stebleton, ). Most scholarship misses this reality, deeming young people incapable of such broad‐based change (Christens & Speer, ).…”
Section: Introductionmentioning
confidence: 99%
“…The literature also consistently pointed to the construction of identity through engagement with specific activist movements. DeAngelo, Schuster, and Stebleton (2016) discussed the identity construction of undocumented students involved with DREAM Act activism. They suggested that students developed a better understanding of self through engagement in activist work associated with a social identity.…”
Section: Student Constructionmentioning
confidence: 99%
“…Indeed, students themselves are sometimes an overlooked group of allies. In that vein, it is essential that the SEM office recognize that undocumented students’ social activism is a way to harness their leadership abilities and pursue self‐empowerment. In fact, research has shown that student activism can lead not only to better outcomes, but to enhanced concern for social justice overall (Chen & Rhoads, ; DeAngelo, Schuster, & Stebleton, ; Munoz & Escalante, ). Remain mindful when facing contradictions within the institution. SEM offices, like any other part of higher education, are made up of people.…”
Section: Inclusive Practice and Student Perceptionsmentioning
confidence: 99%